Directed Dopaminergic Neuron Differentiation from Human Pluripotent Stem Cells - Zhang, Pengbo (J Vis Exp, 2014)
Dopaminergic (DA) neurons in the substantia nigra pars compacta (also known as A9 DA neurons) are the specific cell type that is lost in Parkinson’s disease (PD). There is great interest in deriving A9 DA neurons from human pluripotent stem cells (hPSCs) for regenerative cell replacement therapy for PD. During neural development, A9 DA neurons originate from the floor plate (FP) precursors located at the ventral midline of the central nervous system. Here, we optimized the culture conditions for the stepwise differentiation of hPSCs to A9 DA neurons, which mimics embryonic DA neuron development. In our protocol, we first describe the efficient generation of FP precursor cells from hPSCs using a small molecule method, and then convert the FP cells to A9 DA neurons, which could be maintained in vitro for several months. This efficient, repeatable and controllable protocol works well in human embryonic stem cells (hESCs) and human induced pluripotent stem cells (hiPSCs) from normal persons and PD patients, in which one could derive A9 DA neurons to perform in vitro disease modeling and drug screening and in vivo cell transplantation therapy for PD.